2015
DOI: 10.1016/j.engstruct.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of the behavior, strength and elasticity of masonry in compression

Abstract: The paper focuses on the numerical prediction of the compressive response of masonry by means of detailed micro-modelling techniques. In such a model, the material constituents (mortar and units) and the unit-mortar interfaces are separately described by means of specific constitutive equations.The available modeling choices are evaluated through a literature review of related case studies. A systematic approach is proposed and is corroborated by the numerical simulation of a large number of experimental cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 35 publications
1
55
0
2
Order By: Relevance
“…Any increase in the ratio of mortar increased the elasticity of masonry. This is consistent with the data obtained by Drougkas et al [31] and Gumaste et al [3] who also examined the mor > case as shown in Table 6. Table 8 and Figure 7 illustrate the comparison results of the equivalent elastic moduli based on data obtained by Gumaste et al [3] (see Table 7).…”
Section: Formula Comparisonsupporting
confidence: 92%
“…Any increase in the ratio of mortar increased the elasticity of masonry. This is consistent with the data obtained by Drougkas et al [31] and Gumaste et al [3] who also examined the mor > case as shown in Table 6. Table 8 and Figure 7 illustrate the comparison results of the equivalent elastic moduli based on data obtained by Gumaste et al [3] (see Table 7).…”
Section: Formula Comparisonsupporting
confidence: 92%
“…Although crushing of units is not usual for running bond masonry, however it may occur and affect global collapse mode when units and mortar have comparable compressive strength [6], as in this case. The PIJ and TIJ samples showed similar behaviors.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Current modeling strategy for compressive behavior prediction of masonry structures was validated by research work performed by Drougkas et al [6]. The method is intended to be applied in specimens where units have a higher compressive strength and stiffness than mortar.…”
Section: Resultsmentioning
confidence: 99%
“…Nosúltimos anos, com o crescimento da aplicação de simulação computacional para prever o comportamento de estruturas, diversos modelos numéricos têm sido propostos para representar o comportamento de estruturas de alvenaria submetidasà diversos tipos de carregamentos [Manos et al, 2012, Vandoren et al, 2013, Salát, 2015, Drougkas et al, 2015, Toti et al, 2015, Tesei and Ventura, 2016, Smoljanović et al, 2015, Greco et al, 2016, Milani et al, 2014, Addessi et al, 2014, Macorini and Izzuddin, 2013, Facconi et al, 2013, Addessi and Sacco, 2016, Saloustros et al, 2015a, Bolhassani et al, 2015. Nestes modelos, a principal dificuldade encontrada, tem sido representar o comportamento não linear das juntas de argamassa.…”
Section: Aspectos Gerais E Motivaçãounclassified
“…Nosúltimos anos diversos modelos numéricos têm sido desenvolvidos para modelagem computacional de estruturas de alvenaria [Manos et al, 2012, Vandoren et al, 2013, Salát, 2015, Drougkas et al, 2015, Toti et al, 2015, Tesei and Ventura, 2016, Smoljanović et al, 2015, Greco et al, 2016, Milani et al, 2014, Addessi et al, 2014, Macorini and Izzuddin, 2013, Facconi et al, 2013. O desenvolvimento destes modelos tem sido um desafio, principalmente, por se tratar de uma estrutura complexa, composta por um conjunto de blocos sobrepostos que têm suas interfaces preenchidas por argamassa.…”
Section: Modelagem Numérica De Estruturas De Alvenariaunclassified